Relation between soluble interleukin 2 receptor and clinical findings in patients with systemic lupus erythematosus. Issue 10 (October 1989) - Tokano, Y; Murashima, A; Takasaki, Y; Hashimoto, H; Okumura, K; Hirose, S
Abstract : The concentration of soluble interleukin 2 receptor (IL-2R) was determined in the serum of 54 patients with systemic lupus erythematosus (SLE) by an enzyme linked immunosorbent assay (ELISA) using two monoclonal antibodies with the IL-2R. Concentrations of soluble IL-2R in the serum of the patients with SLE (study group) were significantly higher than in 20 normal subjects (control group). The relation between concentrations of soluble IL-2R and clinical findings was investigated. The concentration of soluble IL-2R showed no particular relation with the clinical manifestations and did not correlate with the level of anti-DNA antibody or CH50. Significant correlation between the concentration of soluble IL-2R and disease activity did exist, however. Furthermore, the concentration of soluble IL-2R in some cases changed simultaneously with the disease activity. Thus the concentration of soluble IL-2R may serve as a new clinical indicator of disease activity in patients with SLE.